2011
DOI: 10.1061/(asce)he.1943-5584.0000280
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall-Runoff Modeling of Three Wadis in the Northern Area of UAE

Abstract: Hydrologic Engineering Center-Hydrologic Modeling System model is used to estimate the water storage in the lakes of three dams due to rainfall events in three wadis located in the northern area of the United Arab Emirates ͑UAE͒. Like other arid and semiarid regions, rainfall events in the three wadis are limited, scattered, and random. For model calibration, the simulated results were compared with the observed water storage data for several storm events. A family of rainfall-runoff/storage curves was develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…HEC-HMS has previously been used to simulate the rainfall-runoff processes in the arid, semi-arid, humid and sub-humid geo-climatic environments in many countries [10][11][12][13]. It has optional models for the sub-mechanisms.…”
Section: Modeling Schemes and Methodologymentioning
confidence: 99%
“…HEC-HMS has previously been used to simulate the rainfall-runoff processes in the arid, semi-arid, humid and sub-humid geo-climatic environments in many countries [10][11][12][13]. It has optional models for the sub-mechanisms.…”
Section: Modeling Schemes and Methodologymentioning
confidence: 99%
“…The United Arab Emirates (UAE) is located in an arid region, with an average annual rainfall of about 110 mm (Sherif et al , 2011. Like other arid regions, drought conditions may prevail for successive years and, hence, surface water resources are mostly regarded as unreliable for water resources planning and management.…”
Section: Introductionmentioning
confidence: 99%
“…Subyani (2011) and Almazroui et al (2012) recently investigated rainfall characterization in Saudi Arabia (arid region). Sherif et al (2009Sherif et al ( , 2011 investigated rainfall properties in three wadi catchments in the United Arab Emirates (UAE). They concluded that rainfall events with durations of 2.5 h or more * Correspondence to: Department of Civil and Environmental Engineering, United Arab Emirates University, Al Ain, United Arab Emirates.…”
Section: Introductionmentioning
confidence: 99%
“…A review of research on tropical rainfall characterization revealed that most of detailed studies were conducted for the humid regions (Jackson, 1977). Whilst few studies were conducted on the UAE rainfall characterization, most of these were spatially extended to a few wadi catchments (Sherif et al, 2011). In this study, rainfall characteristics in the UAE are explored.…”
Section: Introductionmentioning
confidence: 99%